An analysis of successful litigation claims in childhood Fatalities in England. (24th May 2012) - Sen, G; Keene, J; Raine, J
Abstract : Aims: A recent publication analysed successful litigation claims involving children handled by the NHS Litigation Authority (NHSLA). In this study, NHSLA claims in the last 6 years involving a childhood death were investigated. Our aim was to learn from these errors to improve patient safety. Methods: A Freedom of Information request was made to the NHSLA to obtain a record of claims involving fatalities in children from 1st April 2004 to 31st March 2010. The closed cases where compensation had been paid to the claimant were analysed to explore the causes and diseases that led to a fatality and the costs of litigation. Results: 130 out of a total of 234 closed cases (56%) resulted in payment of compensation. These cases were analysed. The commonest causes of a fatality were delayed / failed diagnosis (58), delayed/failed treatment (19), complications related to operations/procedures (17), poor overall quality of care (7), medication errors (6), inappropriate medical advice leading to delayed presentation (6) and communication errors (5). The commonest missed diagnoses were meningitis (10), sepsis - unspecified (8), cardiac defects (7), malignancy (3) and meningococcal septicaemia (3). The total cost of litigation was £8, 143, 342 with cost per case ranging from £1607 to £790, 555 with a mean of £62, 641. Conclusion: A delayed or failed diagnosis was the commonest reason for litigation following a fatality. Meningitis and other forms of sepsis were the most commonly missed conditions. Successful litigation following paediatric deaths has cost the NHS in excess of £8 million since 2004. This data suggests areas where training could be improved. Simulation training is increasingly becoming an integral part of paediatric training, with the aim of improving patient safety, communication and team working. Whilst such training is expensive, if it could reduce errors it may save the NHS from the costs of litigation. The death of a child is a tragedy. When an error has occurred, this causes further suffering to the family and to the healthcare professionals involved. However, by learning from such errors, we can diminish such occurrences in the future.